Delay in diagnosis of blunt abdominal injuries in children and adolescents: a pictorial review of CT abdomen in HTAA - Hassan, Radhiana; Abd. Aziz, Azian; Mohd Yusof, Mubarak; Che Mohamed, Siti Kamariah; Sa'at@Yusof, Azlin; Abdul Rashid, Mohd Amran (2009)
Bluntabdominal injuries are often difficult to be accurately assessed clinically especially with concomitant external injury, in patients with head injury and in paediatric patients1.